Faktor Pendukung dan Penghambat Budaya Keselamatan Pasien di Rumah Sakit: A Systematic Review - Ida Yanriatuti; Nursalam Nursalam; Rr. Soenarnatalina M (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Introduction: Patient safety culture is implemented as an effort to reduce events that can harm patients both physically, materially and psychologically. Objective: To find out the factors that support and hinder the application of patient safety culture in hospitals. Method:Searched databases include Google Scholar, Science Direct, PubMed and Proquest. The criteria of the article are in English language, published in 2016-2020, with the keyword patient safety culture and Hospital Survey on Patient Safety Culture (HSOPSC) Questionnaire. Criteria for selected articles are to be published in 2016-2020 with full text and in English. This Systematic Review uses 15 articles that fit the criteria.Results : Analysis of fifteen articles shows that there are four main factors that both support and hinder the implementation of a patient safety culture namely teamwork, organizational learning, stress levels and nurse burdens, and communication.Conclusion: Several factors support and hinder the application of patient safety culture based on previous research. Suggestion: the factors mentioned from the results of the analysis are deemed necessary to be evaluated and improved to maximize the implementation of patient safety culture. Keywords: supporting factors; inhibiting factor; patient safety culture ABSTRAK Latar belakang: Budaya keselamatan pasien diterapkan sebagai salah satu upaya dalam mengurangi kejadian yang dapat merugikan pasien baik secara fisik, materi maupun psikis.Tujuan: Untuk mengetahui faktor- faktor yang mendukung dan menghambat aplikasi budaya keselamatan pasien di rumah sakit. Metode: pencarian database meliputi Google Scholar, Science Direct, Pub Med dan Proquest dengan kata kunci budaya keselamatan pasien dan koesioner Hospital Survey on Patient Safety Culture (HSOPSC). Kriteria artikel yang dipilih ialah terbit tahun 2016-2020 dengan teks penuh dan berbahasa Inggris.Systematic Review ini menggunakan 15 artikel yang sesuai dengan kriteria. Hasil: Analisis dari lima belas artikel menunjukkan bahwa ada empat faktor utama yang mendukung dan menghambat implementasi budaya keselamatan pasien yaitu kerja tim, pembelajaran organisasi, tingkat stres dan beban kerja perawat,dan komunikasi.Kesimpulan: Terdapat beberapa faktor yang mendukung dan menghambat aplikasi budaya keselamatan pasien berdasarkan penelitian sebelumya.Saran:faktor-faktor yang disebutkan dari hasil analisis dianggap perlu untuk dievaluasi dan ditingkatkan untuk memaksimalkan implementasi budaya keselamatan pasien. Kata kunci: faktor pendukung; faktor penghambat; budaya keselamatan pasien